2017
DOI: 10.1016/s1470-2045(17)30006-2
|View full text |Cite
|
Sign up to set email alerts
|

MABp1 as a novel antibody treatment for advanced colorectal cancer: a randomised, double-blind, placebo-controlled, phase 3 study

Abstract: Total number of:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
106
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 26 publications
2
106
0
Order By: Relevance
“…In an exploratory analysis in a subgroup of patients, the median survival was 6.1 months (95% CI 4.4–7.2) in the MABp1 group compared with only 2.4 months (95% CI 1.9–3.2) in the placebo group, which reinforces the idea that targeting IL-1 pathways is relevant for the treatment of mCRC. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an exploratory analysis in a subgroup of patients, the median survival was 6.1 months (95% CI 4.4–7.2) in the MABp1 group compared with only 2.4 months (95% CI 1.9–3.2) in the placebo group, which reinforces the idea that targeting IL-1 pathways is relevant for the treatment of mCRC. 8 …”
Section: Discussionmentioning
confidence: 99%
“…5,6 Recent clinical data has shown that IL-1 β inhibition using canakinumab could prevent lung cancer growth, 7 and another recent trial has underlined that MAbP1, a monoclonal antibody which targets IL1α, improves quality of life and survival in mCRC. 8 Recently we observed that fluorouracil (5-FU) could activate the NOD-like receptor family, the pyrin domain containing 3-protein (NLRP3)-dependent caspase-1 activation complex (termed the inflammasome) in myeloid-derived suppressor cells (MDSCs), leading to IL-1β production, which curtails anticancer immunity. IL-1β was also shown to induce the generation and expansion of T H 17 cells, which could promote tumor growth by favoring proangiogenesis and immunosuppression in a IL-17A dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Directly targeting the cachexia pathway may prove to be a more successful treatment option [17]. Recently, drugs in newly emerging categories such as MABp1, an IL-1a -specific antibody, and BYM338, an anti-ACVR2B antibody, have been tested in clinical trials [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…There is no dearth of preclinical data to support a role for IL1α in human cancer. Increased survival was reported in a randomized, placebo controlled trial of a neutralizing natural antibody to IL1α in patients with advanced, metastatic colorectal cancer (9). The IL1a precursor is constitutively present in healthy breast cells, and several studies have identified polymorphisms in the IL1α promoter as risk factors in breast cancer.…”
mentioning
confidence: 99%
“…10) and TSLP then contributes to the survival of the tumor cells by increasing Bcl-2 that restricts apoptosis in tumor cells. In that regard, compared with placebo-treated patients, anti-IL1α improved quality of life as well as increased survival (9). …”
mentioning
confidence: 99%